PROBLEMATICS OF THE OVERSIGHT OF THE CODE OF CONDUCT AND THE CODE OF JUDGMENT BETWEEN THE JUDICIAL COMMISSION AND THE SUPREME COURT - Siti Kotijah; Muhammad Rizki An Noor; Ine Ventyrina; Poppilea Erwinta (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
The research objective is to capture the joint examination mechanism which is the control between the Judicial Commission and the Supreme Court. This research uses a doctrinal approach which is based on the existence of a problem that is examined in the laws and regulations, the Code of Ethics and Code of Conduct of Judges, the problems of monitoring the Code of Ethics and the Code of Conduct of Judges in the context of the current joint examination, it is necessary to remove them, as concrete steps taken to improve a supervisory system for the Code of Ethics and Code of Conduct for Judges in the future. Ius the contituendum of supervision between KY and MA as a new formulation of the KY Bill. This method uses a doctrinal (normative) approach because it has a research target in the form of a set of norms. Approach in statutory research, and concept approach. The result is legal implications of the presence of joint examinations in the supervision of the Code of Ethics and the Code of Conduct of Judges between the Judicial Commission and the Supreme Court.